Understanding the sport-nutrition knowledge and practices among Jordanian olympic preparation program's athletes and coaches for TOKYO2020 Olympic Games - Amawi, A. T.; AbuAwad, B.; Alshuwaier, G. O.; Alnuaim, A. A.; Bursais, A. K.; Alaqil, A. I. (International Journal of Human Movement and Sports Sciences, 2022)
Despite the importance of physical activity and training, proper nutrition and good nutrition knowledge plays an important role in enhancing the athletes' performance and health status.